Retinal nerve fiber layer and ganglion cell complex thickness assessment in patients with Alzheimer disease and mild cognitive impairment. Preliminary results - A. S. Tiganov; V. S. Akopyan; S. I. Gavrilova; N. S. Semenova; Ya. B. Fedorova; E. V. Gurova (Oftalʹmologiâ, 2014)
Purpose: to investigate the retinal nerve fiber layer (RNFL) and the macular ganglion cell complex (GCC) in patients with Alzheimer`s disease and mild cognitive impairment.Methods: this study included 10 patients (20 eyes) with Alzheimer`s disease, 10 patients with mild cognitive impairment and 10 age- and sex-matched healthy controls that had no history of dementia. All the subjects underwent psychiatric examination, including the Mini-Mental State Examination (MMSE), and complete ophthalmological examination, comprising optical coherence tomography and scanning laser polarimetry.Results: there was a significant decrease in GCC thickness in patients with Alzheimer`s disease compared to the control group, global loss volume of ganglion cells was higher than in control group. there was no significant difference among the groups in terms of RNFL thickness. Weak positive correlation of GCC thickness and MMSE results was observed.Conclusion: Our data confirm the retinal involvement in Alzheimer`s disease, as reflected by loss of ganglion cells. Further studies will clear up the role and contribution of dementia in pathogenesis of optic neuropathy.